2021
DOI: 10.1186/s43044-021-00153-w
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of serum TGF-beta levels and associated polymorphisms in patients with coronary artery ectasia and normal coronary artery

Abstract: Background Coronary artery ectasia (CAE) is described as the enlargement of a coronary artery segment by 1.5 times or more, which is generally associated with the atherosclerotic process. Atherosclerotic changes lead to arterial remodeling result in CAE. In our study, we measured serum transforming growth factor (TGF)-β1 levels, which have a protective role against atherosclerosis. Further, we aimed to assess the TGF-β1 gene variants rs1800469 (–509C>T, c.−1347C>T) and rs1800470 (c.+29T&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Similar concentrations in DAA and NDAA patients can be attributed to the aortic valve and ascending aorta developing from neural crest cells during embryonic development ( 31 – 34 ). TGF-β1 levels were lower in the coronary artery ectasia group than in the control group, according to Ser et al ( 35 ). This information provided us with additional information indicating possible similarities in the ascending aorta’s anatomical structures.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Similar concentrations in DAA and NDAA patients can be attributed to the aortic valve and ascending aorta developing from neural crest cells during embryonic development ( 31 – 34 ). TGF-β1 levels were lower in the coronary artery ectasia group than in the control group, according to Ser et al ( 35 ). This information provided us with additional information indicating possible similarities in the ascending aorta’s anatomical structures.…”
Section: Discussionmentioning
confidence: 76%
“…When patients were divided into groups based on aortic valve phenotype, there was no statistically significant difference in TGF-β1 levels between DAA-TAV and DAA-BAV [30.39 (24.1-37.44) vs. 37. 35 TGF-β1 concentrations in patients with dilated and non-dilated aortas according to aortic valve cuspidity. CG, control group; DAA-TAV, dilated ascending aorta-tricuspid aortic valve; DAA-BAV, dilated ascending aorta-bicuspid aortic valve; NDAA-TAV, non-dilated ascending aorta-tricuspid aortic valve; NDAA-BAV, non-dilated ascending aorta-bicuspid aortic valve.…”
Section: Resultsmentioning
confidence: 99%
“…A study reported low serum TGF-β concentration in cats with CKD compared with healthy cats, but the findings were not significant. 18 Regarding other diseases, serum TGF-β1 concentration was significantly lower in human patients with thrombocytopenia 31 and coronary artery disease 32,33 than in controls. TGF-β1 is produced by megakaryocytes, stored in platelet alpha-granules and released in serum by degranulation.…”
Section: Discussionmentioning
confidence: 98%
“…Even though AhR agonists, TGF-β, and RA are naturally present at mucosal sites and contributes to tolerance induction, injecting the combination of IGN-512, TGF-b, and RA systemically is not considered a viable option because of the risk of toxicity as the concentrations used for the generation of ItolDCs are higher than what if found in normal serum levels ( 61 , 62 ). Further, it will be very difficult to accomplish antigen-specific tolerance following systemic injection of the antigen, unless the compounds are encapsulated ( 63 ), e.g.…”
Section: Discussionmentioning
confidence: 99%